Interruptoras: asepsia digital y tecnopoéticas responsables en las escritoras hispánicas - Sánchez-Aparicio, Vega (Diálogos Latinoamericanos, 2022)
If we think about digital materiality in printed texts, we can approach this work from three basic questions: how is a feminist language articulated from the ‘abstract masculinity’ (Hartsock) of algorithms? Can software be feminist? Can the materiality of code be moved? Thus, this text will review writing practices in Spanish produced by women —specifically the works of Cristina Rivera Garza (Tamaulipas, 1964), María Ángeles Pérez López (Valladolid, 1967) and Verónica Gerber Bicecci (Ciudad de México, 1981)— who have developed an ethical discourse. Their aesthetics, dissident from the rhetoric of software, aim to make visible and, consequently, subvert hegemonies, roles and gender stereotypes that still persist in contemporary culture.